Aldehydes-Aided Lignin-First Deconstruction Strategy for Facilitating Lignin Monomers and Fermentable Glucose Production from Poplar Wood - Tian-Ying Chen (Energies, 2020)
In this study, lignin with fine structures and facile enzymatic saccharifying residue were successively dissociated based on the lignin-first biomass deconstruction strategy. In the lignin-first process, aldehyde-protected lignin fractions were firstly isolated by acid-catalyzed dioxane extraction in the presence of formaldehyde (FA) and acetaldehyde (AA) and then analyzed by advanced nuclear magnetic resonance (NMR) spectroscopy and gel permeation chromatography (GPC). The optimized hydrogenolysis of the extracted lignin (LFA and LAA) resulted in a high yield (42.57% and 33.00%) of lignin monomers with high product selectivity (mainly 2,6-dimethoxy-4-propylphenol) (39.93% and 46.61%). Moreover, the cellulose-rich residues were saccharified into fermentable glucose for bioethanol production. The glucose yield of the substrate (RAA) reached to 75.12%, which was significantly higher than that (15.4%) of the substrate (RFA). In short, the lignin-first biomass deconstruction by adding AA is a promising and sustainable process for producing value-added products (energy and fine chemicals) from lignocellulosic biomass.